A Conceptual Study on Factors of Entrepreneurial Potentiality and their Impact on Entrepreneurial Intention with the Moderating Role of Entrepreneurship Education - Aggarwal, Vaneeta (Prabandhan: Indian Journal of Management, 2019)
Entrepreneurship plays a very significant role in the social and economic development of a country. This research study built a model on antecedents of entrepreneurial intention constructs, which were validated in various studies on entrepreneurship. With a thorough review of literature, reflecting and importing from the existing theories and studies, I found the antecedents of entrepreneurial intention and segregated them into psychological factors, social factors, and institutional factors with reference to past studies. As a result of the thorough literature review of previous studies, I grouped creativeness, decision making skills, passion, locus of control, risk-taking propensity, tolerance of ambiguity, need for achievement, and self-efficacy under psychological factors. The variables: family support, mentoring, networking, and peer group influence were grouped under social factors. The variables: entrepreneurship awareness programs, guiding material, and awareness of government schemes were grouped under institutional factors. Clubbing all these three factors, I coined the term 'Entrepreneurial Potentiality'. The proposed conceptual model delineated the role of entrepreneurial education as a moderator. This conceptual research paper is exhaustive in nature, widening its scope right from the seminal papers to the recent ones, and as a result, all the determinants of entrepreneurial potentiality were explicitly defined. An integrated approach was used to examine the complex interplay of the concept of entrepreneurial intention.